Perancangan Interior Gedung Teater pada Pengembangan Kompleks Taman Budaya Jawa Timur di Surabaya - Thio, James; Yusita Kusumarini; Anik Rakhmawati (Intra, 2018)
Surabaya is the capital of East Java province that has unique culture and art. Arts such as ludruk, ketoprak, kentrung, wayang wong, janger and darmawulan become famous nowadays. The East Java theater building in Surabaya needs a design that attracts public to watch art performances. By applying a design that has a not-too-large capacity, it is expected to be an appropriate facility for the show and the audience. The design problem is how to design a theater that applies modern technology to invite the public appreciating the theater art, especially young people.The method used is the stages of design thinking including understanding, observe, point of view, ideate, prototype, test, implementation. Theater design with a touch of technology is expected to attract young people. The technology is an interactive floor used on stage. The screen on the floor can move when the sensor catches motion. In the lobby, there are information facilities about ludruk art and others.